Ultrahigh‐Sensitive Broadband Photodetectors Based on Dielectric Shielded MoTe2/Graphene/SnS2 p–g–n Junctions. Issue 6 (14th December 2018) - Li, Alei; Chen, Qianxue; Wang, Peipei; Gan, Yuan; Qi, Tailei; Wang, Peng; Tang, Fangdong; Wu, Judy Z.; Chen, Rui; Zhang, Liyuan; Gong, Youpin
Abstract: 2D atomic sheets of transition metal dichalcogenides (TMDs) have a tremendous potential for next‐generation optoelectronics since they can be stacked layer‐by‐layer to form van der Waals (vdW) heterostructures. This allows not only bypassing difficulties in heteroepitaxy of lattice‐mismatched semiconductors of desired functionalities but also providing a scheme to design new optoelectronics that can surpass the fundamental limitations on their conventional semiconductor counterparts. Herein, a novel 2D h‐BN/p‐MoTe2 /graphene/n‐SnS2 /h‐BN p–g–n junction, fabricated by a layer‐by‐layer dry transfer, demonstrates high‐sensitivity, broadband photodetection at room temperature. The combination of the MoTe2 and SnS2 of complementary bandgaps, and the graphene interlayer provides a unique vdW heterostructure with a vertical built‐in electric field for high‐efficiency broadband light absorption, exciton dissociation, and carrier transfer. The graphene interlayer plays a critical role in enhancing sensitivity and broadening the spectral range. An optimized device containing 5−7‐layer graphene has been achieved and shows an extraordinary responsivity exceeding 2600 A W −1 with fast photoresponse and specific detectivity up to ≈10 13 Jones in the ultraviolet–visible–near‐infrared spectrum. This result suggests that the vdW p–g–n junctions containing multiple photoactive TMDs can provide a viable approach toward future ultrahigh‐sensitivity and broadband photonic detectors. Abstract : h‐BN/MoTe2 /graphene/SnS2 /h‐BN van der Waals heterostructure photodetectors present an extraordinary broadband responsivity exceeding 2.6 × 10 3 A W −1 and detectivity up to ≈10 13 Jones in a wide spectrum, which is attributed to the enhanced light absorption and highly effective exciton dissociation originating from the vertical built‐in electric field and multiple photoactive layers in the unique heterostructures.